FARMING DEVELOPMENT STRATEGY IN COCONUT IN POHUWATO REGENCY - Gaga, Amran (Universitas Negeri Gorontalo, 2021)
The purpose of this study were: 1) Analyzes the factors that influence the development of coconut cultivation in Pohuwato; 2) Coconut farming development strategy in Kabuoaten Pohuwato.The study was conducted in Pohuwato of the month December 2019 until February 2020 with a sample of 40 farmers. The method used is a survey method possible. Analysis of the data used is analysis SWOT. The results showed that the factors that influence the development of coconut in Pohuwato namely internal and external factors that influence the development strategy of the Coconut Pohuwato that internal factors are replaced plant coconut, oil prices often fluctuate, the lack of rejuvenation of coconut plantations and processing farms palm are still traditional. While external factors are unpredictable weather conditions which cause crop failure, there is no pricing dassar coconut and coconut farmers besides farming. The development strategy of coconut in Pohuwato which is located in Quadrant I, which supports the strategy Aggressive or S-O strategy (strenght - opportunity) by using the strength of such experience or the ability of farmers, as well as take advantage of existing opportunities such as coconut plants have good market prospect, to minimize weakness as oil prices frequently fluctuate, then the existing threats as there is no basic pricing oil and erratic climate conditions so that the development of coconut cultivation achieve progress.